Emerging Trends of Nanomedicines in the Management of Prostate Cancer: Perspectives and Potential Applications - Rohitas Deshmukh; Vaibhav Singh; Ranjit K. Harwansh; Rutvi Agrawal; Akash Garg; Sudarshan Singh; Gehan M. Elossaily; Mohd Nazam Ansari; Nemat Ali; Bhupendra G. Prajapati (Pharmaceutics, 2024)
Prostate cancer is one of the most life-threatening disorders that occur in males. It has now become the third most common disease all over the world, and emerging cases and spiking mortality rates are becoming more challenging day by day. Several approaches have been used to treat prostate cancer, including surgery, radiation therapy, chemotherapy, etc. These are painful and invasive ways of treatment. Primarily, chemotherapy has been associated with numerous drawbacks restricting its further application. The majority of prostate cancers have the potential to become castration-resistant. Prostate cancer cells exhibit resistance to chemotherapy, resistance to radiation, ADT (androgen-deprivation therapy) resistance, and immune stiffness as a result of activating tumor-promoting signaling pathways and developing resistance to various treatment modalities. Nanomedicines such as liposomes, nanoparticles, branched dendrimers, carbon nanotubes, and quantum dots are promising disease management techniques in this context. Nanomedicines can target the drugs to the target site and enhance the drug’s action for a prolonged period. They may also increase the solubility and bioavailability of poorly soluble drugs. This review summarizes the current data on nanomedicines for the prevention and treatment of prostate cancer. Thus, nanomedicine is pioneering in disease management.